(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
Triyan Hardiyanti conducted research in 2024 regarding the effectiveness of using short English films in improving the listening skills of class IX.4 students at SMPN 23 Makassar. This research followed Kemmis and McTaggart’s classroom action method and was carried out in two cycles, involving 32 students. Data was collected through tests, teacher journals, and observations. The results showed significant improvements in students’ listening skills; from only 31.25% of students who achieved the Minimum Completion Criteria (KKM) in the pre-test to 53.12% in cycle I and 84.37% in cycle II, with the average score increasing from 80.31 to 90.93 . Positive responses from teachers and students towards the use of films in learning confirm that this method is effective for improving students’ listening skills